МЕТАФОРИЧЕСКОЕ МОДЕЛИРОВАНИЕ НЕПРОСТРАНСТВЕННЫХ СФЕР В СОВРЕМЕННОМ АНГЛИЙСКОМ ЯЗЫКЕ - Shamne, Nikolay Leonidovich; Yanina, Viktoriya Viktorovna (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2014)
In the scope of cognitive approach, the article studies the spatial metaphor as a way of understanding and nomination of objects and phenomena of directly not observed social, mental and intellectual spheres, the status and the functional importance of nouns denoting limited space for these processes. The authors describe the set of English polisemantic spatial nouns denoting limited space, reveal semantic multipliers in their basic meaning, define the metaphorical and axiological meanings of polysemants, consider semantic modifications of spatial nouns and describe the models of metaphorical shifts on the basis of re-thinking spatial features. The metaphorical shift of spatial characteristics onto the events and phenomena of social sphere is the most frequent (68, 58 %), as it is realized in most regular metaphorical models. The metaphorical shift of spatial characteristics onto the mental phenomena is marked by lower frequency (24, 28 %), and as a result it is realized in smaller number of metaphorical models. The metaphorical shift of spatial characteristics onto intellectual sphere is marked by the lowest frequency (7, 14 %). It is represented by the minimal number of regular metaphorical models. The authors determine the connection between spatial features and evaluation sphere and reveal the spatial features which prove to be essential in evaluation process. The article shows that from the wide range of semantic multipliers which characterize limited fragment of space, the following spatial features are actualized: "size", "border", "configuration", "loading", "functional characteristics", "constituents", "coordination parameters" and "structural characteristics".